The Limits of EU Market Power in Migration Externalization: Explaining Migration Control Provisions in EU Preferential Trade Agreements - Paula Hoffmeyer-Zlotnik; Sandra Lavenex; Philipp Lutz (JCMS: Journal of Common Market Studies, 2023)
The European Union (EU) increasingly seeks cooperation with transit and sending countries to prevent irregular migration and enforce returns. Yet, these countries have little incentives to engage in such cooperation. To overcome interest asymmetries, the EU has sought to link trade and migration control in its preferential trade agreements (PTAs). Drawing on a comprehensive dataset of migration provisions in all PTAs signed between 1960 and 2020 and a qualitative analysis of key policy documents, we show that the inclusion of such provisions does not follow patterns of interdependence and strategic priorities resulting from problem pressure. Rather, the proliferation of migration control provisions in EU PTAs is best explained by the institutional framework guiding the negotiation of these provisions. Whilst reflecting the political will to use PTAs as a 'carrot' to incite third-country cooperation, these findings also show the limits of targeted action on migration control via commercial policies.
Keywords: 330; European Union; externalization; free trade agreements; migration policy; non-trade policy objectives